Effect of Caralluma tuberculata on regulation of carbohydrate metabolizing genes in alloxan-induced rats. (10th May 2021) - Aslam, Maria; Syed, Nawazish-i-Husain; Jahan, Shah
Abstract: Ethnopharmacological relevance: Caralluma tuberculata ( C. tuberculata ) has traditionally been used in Pakistan and other parts of the world as a folk treatment for diabetes mellitus. A few studies indicated its antihyperglycemic effect, however, the mystery remained unfolded as how did it modify the pathophysiological condition. Aim of study: Hence, this study aimed to explore underlying mechanism(s) for its hypoglycemic activity at biochemical and molecular levels. Materials and methods: Methanol extract (ME) of C. tuberculata as well as its hexane (HF) and aqueous (AF) fractions were explored for their effect on total glycogen in liver and skeletal muscle of alloxan-induced rats by spectroscopy. Moreover, the expression of genes related to hepatic carbohydrate metabolizing enzymes was quantified. At molecular level, mRNA expression of glucose transporter 2 (GLUT-2), glycogen synthase (GS), glucokinase (GK), hexokinase 1 (HK-1), pyruvate kinase (PK), glucose 6 phosphate dehydrogenase (G-6-PDH), pyruvate carboxylase (PC), phosphoenolpyruvate carboxykinase (PEPCK) and glucose 6 phosphatase (G-6-Pase) was determined by using quantitative real time polymerase chain reaction (qRT-PCR) after administration of ME (350 mg), HF(3 mg), AF (10 mg) and metformin (500 mg). The doses were administered twice daily according to per kg of body weight. Results: A significant reduction in hepatic and skeletal muscle glycogen content was exhibited. The data of qRT-PCR revealed that gene's expression of GLUT-2 was significantly decreased after treatment with ME and HF, whilst it was unaltered by AF, however, a significant decrease was observed in genes corresponding to GS, GK and HK-1 after treatment with ME. Similarly, there was a significant decrease in expression of genes corresponding to GS, GK and HK-1 following treatment with HF. Surprisingly, post-treatment with AF didn't modify the gene's expression of GS and GK, whilst it caused a profound decrease in expression of HK-1 gene. Contrarily, the expression of gene related to PK was significantly up-regulated post-administration with ME, HF and AF. The expression levels of G-6-PDH, however, remained unaltered after treatment with the experimental extract and fractions of the plant. In addition, HF and AF did not cause any modification in PEPCK, whereas ME caused a significant down-regulation of the gene. Treatment with all the extract and fractions of the plant caused a substantial decrease in the gene's expression of PC, while there was a significant increase in the expression of gene related to G-6-Pase. Conclusion: The three experimental extract and fractions caused a substantial decrease in glycogen content in liver and skeletal muscle tissues. The analysis by qRT-PCR showed that glucose transport via GLUT-2 was profoundly declined by ME and HF. The expression of genes related to various metabolic pathways involved in metabolism of carbohydrate in hepatocytes revealed explicitly that the ME, HF and AF decreased the phenomena of glycogenesis and gluconeogenesis. Contrarily, all the extract and fractions of the plant activated glycogenolysis and glycolysis but did not modify the pentose phosphate shunt pathway. Graphical abstract: Image 1 Highlights: Extract and fractions of C. tuberculata  showed antihyperglycemic activity, however signalling mechanisms remained unexplored. These were investigated for effects on genes involved in glycogenesis, glycolysis, PPSP, gluconeogenesis and glycogenolysis. The effect of extract and fractions of plant can well be seen by down and up-regulation of genes related to above phenomena. C. tuberculata  decreased the glycogen in liver and skeletal muscle, in addition to GLUT-2, glycogenesis and gluconeogenesis. The phenomena of glycogenolysis and glycolysis were however activated by the experimental extract and fractions of the plant.